Africans in East Anglia, 1467-1833 - Maguire, Richard, 1966- (Studies in early modern cultural, political and social history., 2021)
What were the lives of Africans in provincial England like during the early modern period? How, where, and when did they arrive in rural counties? How were they perceived by their contemporaries?